Filling carbon nanotubes with small palladium metal crystallites: The effect of surface acid groups - Lago, R; Tsang, S; Lu, K; Chen, Y; Green, M (1995)
The filling of carbon nanotubes with palladium metal crystallites is described and it is shown that when the carbon nanotube samples are opened using nitric acid, surface acid groups (CO2H and OH) are present on both the nanotubes and nanoparticles and these interact strongly with palladium ions: ultrasound pre-treatment of the carbon nanotube samples prior to the oxidation with nitric acid increases the number of these groups.